2017
DOI: 10.1515/jtim-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic encephalopathy in liver cirrhosis

Abstract: Liver cirrhosis is a worldwide gastroenterological condition, characterized by a slow, progressive and irreversible replacement of liver cells by fibrous tissue (scar) that prevents liver function. This condition often leads to the development of other syndromes. Cardiac complications can be indicated through abnormal QTc interval and arrhythmias, thereby their analysis aids in the prevention of cardiovascular events. Most cirrhotic cases have abnormal laboratory values (bilirubin, albumin, AST, ALT, AST/ALT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…After the metal stent is placed, tumor invasion or overgrowth, bile accumulation, or biofilm formation may cause clogging in the stent. In this study, the median patency time of a simple metal stent was 7 mo in patients with high biliary obstruction, which is similar to that of other previous studies[16,17,29,30](7-9 mo).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…After the metal stent is placed, tumor invasion or overgrowth, bile accumulation, or biofilm formation may cause clogging in the stent. In this study, the median patency time of a simple metal stent was 7 mo in patients with high biliary obstruction, which is similar to that of other previous studies[16,17,29,30](7-9 mo).…”
Section: Discussionsupporting
confidence: 90%
“…Obstructive jaundice is a common clinical symptom of hilar cholangiocarcinoma. Persistent biliary obstruction can lead to liver failure, secondary renal failure[27,28], severe hypoproteinemia, electrolyte imbalance, septic shock, etc ., affecting the quality of life and survival of patients[16,29,30]. Clinically, percutaneous drainage tube or biliary stent implantation in various ways is an effective treatment for obstructive jaun-dice[17,31-39].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, prolongation of INR has been observed in studies conducted in the USA and HE with liver cirrhosis in Ukraine (15,16). Similarly, in the study conducted by Koch et al, the INR level was found to be longer than normal in cases with HE resulting in death (16).…”
Section: Discussionmentioning
confidence: 51%
“…Our study includes patients with chronic liver disease who developed HE due to acute failure. In other studies from Ukraine and America, ALT and AST values were found to be increased when blood ammonia level increased (15,16).…”
Section: Discussionmentioning
confidence: 62%
“…The aetiology of cirrhosis varies geographically with Alcoholic liver disease, Chronic Hepatitis C Virus (HCV) infection, and nonalcoholic fatty lives disease (NAFLD) being the most common causes in western countries, whereas chronic hepatitis B and C are the primary cause of liver cirrhosis in the Asia-Pacific region. 1,2 Liver cirrhosis is associated with a number of complications that can even lead to mortality but the most common complication is portosystemic encephalopathy that results in significant mortality. 3 Hepatic encephalopathy is defined as a spectrum of neuropsychiatric abnormalities in patients with liver dysfunction, after exclusion of other known brain diseases.…”
Section: Introductionmentioning
confidence: 99%